ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA ANAK DI PUSKESMAS ANDALAS KOTA PADANG - Tisnawati Tisnawati; Sonia Komala Dewi; Zolla Amely Ilda; Metri Lidya; Delima Delima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
A number of serious health problems among children are caused by diarrhea, such as dehydration, hypovolemic shock, hypokalemia, seizures, malnutrition and even death. Padang was in on the fourth highest of diarrheal incident in 2020 which reached the percentage of 10.44%. This study aimed to determine the factors related to diarrheal incident in work area public health center of Andalas in Padang. The research used cross sectional design that was started from January to June 2022. The research population was 125 mothers who came to Mother and Child Healthcare polyclinic of Andalas Public Health Center, with the total sample of 55 people using accidental sampling technique. This study used Analysis with Chi square test which was 95% CI. The results showed that there was a relationship between exclusive breastfeeding and knowledge of p-value (0.004), CTPS p- (0.004), and exclusive breastfeeding p-value (0.007). Suggested to public health center workers to conduct continuous cooperation through the health promotion in order to prevent this issue.